A translational review of hyperthermia biology - Mark W. Dewhirst (International Journal of Hyperthermia)
This review was written to be included in the Special Collection ‘Therapy Ultrasound: Medicine’s Swiss Army Knife?’ The purpose of this review is to provide basic presentation and interpretation of the fundamentals of hyperthermia biology, as it pertains to uses of therapeutic ultrasound. The fundamentals are presented but in the setting of a translational interpretation and a view toward the future. Subjects that require future research and development are highlighted. The effects of hyperthermia are time and temperature dependent. Because intra-tumoral temperatures are non-uniform in tumors, one has to account for differential biologic effects in different parts of a tumor that occur simultaneously during and after hyperthermia.